Optimized Treatment of Nosocomial Peritonitis - Jan J. De Waele; Federico Coccolini; Leonel Lagunes; Emilio Maseda; Stefano Rausei; Ines Rubio-Perez; Maria Theodorakopoulou; Kostoula Arvaniti (MDPI AG, 2023)
This comprehensive review aims to provide a practical guide for intensivists, focusing on enhancing patient care associated with nosocomial peritonitis (NP). It explores the epidemiology, diagnosis, and management of NP, a significant contributor to the mortality of surgical patients worldwide. NP is, per definition, a hospital-acquired condition and a consequence of gastrointestinal surgery or a complication of other diseases. NP, one of the most prevalent causes of sepsis in surgical Intensive Care Units (ICUs), is often associated with multi-drug resistant (MDR) bacteria and high mortality rates. Early clinical suspicion and the utilization of various diagnostic tools like biomarkers and imaging are of great importance. Microbiology is often complex, with antimicrobial resistance escalating in many parts of the world. Fungal peritonitis and its risk factors, diagnostic hurdles, and effective management approaches are particularly relevant in patients with NP. Contemporary antimicrobial strategies for treating NP are discussed, including drug resistance challenges and empirical antibiotic regimens. The importance of source control in intra-abdominal infection management, including surgical and non-surgical interventions, is also emphasized. A deeper exploration into the role of open abdomen treatment as a potential option for selected patients is proposed, indicating an area for further investigation. This review underscores the need for more research to advance the best treatment strategies for NP.